2007
DOI: 10.1007/s10661-007-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride contamination in drinking water in rural habitations of Northern Rajasthan, India

Abstract: This study was carried out to assess the fluoride concentration in groundwater in some villages of northern Rajasthan, India, where groundwater is the main source of drinking water. Water samples collected form deep aquifer based hand-pumps were analysed for fluoride content. Fluoride in presently studied sites was recorded in the ranges of 4.78 and 1.01 mg/l. The average fluoride concentration for this region was recorded 2.82 mg/l. As per the desirable and maximum permissible limit for fluoride in drinking w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…Since an interaction between F bearing minerals in host rocks and water is known to control F concentration in bathing solution. Suthar et al (2007), however, observed significant variations in F concentration in groundwater along depth.…”
Section: Resultsmentioning
confidence: 84%
“…Since an interaction between F bearing minerals in host rocks and water is known to control F concentration in bathing solution. Suthar et al (2007), however, observed significant variations in F concentration in groundwater along depth.…”
Section: Resultsmentioning
confidence: 84%
“…The high frequency of superposition of arseniasis with Xuorosis was conWrmed. The Xuorosisarseniasis co-endemic related with the unique exposure scenario represents a rare situation and greatly diVers from the exposure via Xuorine-or arsenic-contaminated drinking water which happened in most other endemic areas in this country (Jin et al 2003;Hao et al 2002;Zhu et al 2006;Zhao et al 2006;Zha et al 2005;Guo et al 2006;Lan et al 2008) and along the world as well (Armienta and Segovia 2008;Oruc 2008;Suthar et al 2008;Rahman et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a clear need to take chemical contaminants into account in developing risk management strategies for the safety of drinking water (WHO 2007). Fluoride in drinking water has appeared as a serious problem, and around 200 million people, from among 25 nations the world over, are under the dreadful fate of fluorosis (Suthar et al 2008a;Garg et al 2009). Fluoride is endemic for the Indian subcontinent.…”
Section: Safe Drinking Water: Some Quality Issuesmentioning
confidence: 99%